Between Self and Deadlines: Students' Battle to Preserve Mental Health - Nurjulianti Nurjulianti; Fifi Angraini; Riska Romadhona; Sandi Pradana (SocioSphere: Interdisciplinary Journal of Social Sciences and Humanities, 2025)
This study aims to examine the struggles of UIN Syahada students in maintaining mental health amidst the pressure of academic assignment deadlines. The methodology employed is qualitative with data collection techniques through in-depth interviews and participatory observation of several active students. The results indicate that students face significant challenges in managing stress and time pressure, but they strive to develop coping strategies such as time management, sharing feelings with friends, and engaging in relaxation activities. These findings emphasize the importance of social support and awareness of mental health among students as part of preventive efforts against academic stress. Academic pressure is often a significant source of psychological burden for university students, Affecting their mental health and emotional stability. This study aims to explore the strategies used by students to maintain inner balance amidst demanding academic responsibilities. A descriptive Qualitative approach was employed, using in-depth interviews with ten students from various Departments at a public university. The findings reveal that students cope with stress through several methods, such as meditation, religious practices, time management, and social support from family and peers. The study also found that students with strong self-awareness and environmental support are more likely to maintain emotional stability. It concludes that mental health efforts within campus life should not rest solely on individual responsibility but also require systemic support from Educational institutions. These results are expected to serve as input for universities to provide Spaces and policies that support students' psychological well-being in a sustainable manner.